RANCANG BANGUN MEDIA PEMBELAJARAN IPA (AYO MENGENAL HEWAN DAN TUMBUHAN) UNTUK KELAS 4 SD BERBASIS ANDROID - Yogiyana Aditama; Devi Afriyantari Puspa Putri (STMIK Sinar Nusantara, 2019)
Natural science is one of the subject the related to daily life, that learned by student such grouping of animals, the life cycle of animals and plants. However in the learning process students are less motivated because the study method are less attractive. According to these problems natural science media using android platform was made for 4th grade student because students still have a high interest in Android smartphones and animation. The purpose of the study is to produce interactive and interesting media for learning, so the students can learn natural science easily and pleasantly. Waterfall method used in designing process. The testing phase in this study uses black box testing method and user acceptance test with students and teachers as respondence. The overall result for testing and questionnaire has the average 93,4%. It can be concluded that the application can run as expected and can be used as a media of learning for students.